The Use of Persuasive Sentences in Copywriting - Christinawati, Santy; Trimastuti, Wahyu; Latifah, Anita; Alpina, Bela; Angelika, Eka (Pendidikan Bahasa Inggris (Universitas Internasional Batam), 2023)
This research is about the use of persuasive sentences in copywriting. The purpose of this research is to identify the use of persuasive sentences in copywriting. The data used in this study were obtained by taking several examples of marketing posters for a product from several sales sources. The results show that persuasive sentences are widely used as a copywriting technique. Keywords: persuasive sentences, copywriting, market poster.